(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
A brief description of seven benthic environments found in La Guajira’s shallow continental shelf from Boca de Camarones to Cabo de la Vela between 3 to 20 m depth is presented. Cover percentage of main benthic components, organic matter proportion in sediment, and main organisms observed in each environment are listed. The dominant environment was “arenal” (sandy bottom) covering 47% of total area sampled, whereas most species were observed in the environments “fondo mixto” (mixed bottom), “cascajo compuesto” (composed gravel) and “corales y esponjas sobre cascajo” (corals and sponges on gravel).